Data centres as logistical facilities: Singapore and the emergence of production topologies. (1st April 2019) - Neilson, Brett; Notley, Tanya
Abstract : Data centres mobilise server-client architectures to disperse and draw in labour from across industries and nations. In doing so, they provide an infrastructural fix for capitalist actors seeking to bypass traditional labour actions, by designing logistical routes around which to redirect production processes. In this article, we build on research that investigates the data centre industry in Singapore to consider how these facilities drive processes of global circulation and establish new kinds of labour relations and processes. We point to limits in conceptualising these relations according to dominant models of the supply chain or the production network. We argue that understanding the client footprint enabled by data centres as a form of territory allows us to approach these facilities as political institutions that influence the operations of power across wide geographical vistas.